(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This research will explain the role of the Bekasi Hezbollah Army in maintaining the independence of the Republic of Indonesia in 1945-1947, from the formation, development, to fusion with the TNI. The research methods used in this study are historical methods such as source search, source criticism, interpretation, and historiography. The findings in this article are, in 1945 the Laskar Hizbullah Bekasi was formed by Angkut Abu Gozali and K.H. Noer Ali in Tambun, the formation was a follow up of the Hezbollah Laskar education alumni conducted in Cibarusah from February to May 1945. The Bekasi Hezbollah Army had the structure of the Abu Gozali Transport (Commander of IV Hezbollah Regiment of Bekasi), H. Usman Lemahabang (Commander Battalion I Lemahabang), Abdullah Syair (Commander of Battalion II Pondok Ungu, and Kiai Noer Ali (Commander of Battalion III Ujung Malang), each battalion was in charge of several companies.The Bekasi Hezbollah Warriors consisted of youths with santri and jawara backgrounds. In 1947, there were many battles in Bekasi involving the Hezbollah Army of Bekasi facing an Allied force attack, showing that the Bekasi Hezbollah Army was one of the class struggle bodies that played an important role in maintaining the independence of the Republic of Indonesia in 1945-1947.